Titanium and Zirconium Base Alloys in Ultra-Fine Grain State: Mechanical Stability and Failure Behavior; Key Engineering Materials; Vol. 683 : Multifunctional Materials: Development and Application - Danilov V. I. Vladimir Ivanovich; Eroshenko A.; Sharkeev Yu. P. Yury Petrovich; Orlova D. V. Dina Vladimirovna; Zuev L. B. (Physicochemical Properties of Materials and Current Processing Technologies, 2016)
Title screen